Cover Picture: tert‐Butylcarbamate‐Containing Histone Deacetylase Inhibitors: Apoptosis Induction, Cytodifferentiation, and Antiproliferative Activities in Cancer Cells (ChemMedChem 5/2013). Issue 5 (26th April 2013) - Valente, Sergio; Trisciuoglio, Daniela; Tardugno, Maria; Benedetti, Rosaria; Labella, Donatella; Secci, Daniela; Mercurio, Ciro; Boggio, Roberto; Tomassi, Stefano; Di Maro, Salvatore; Novellino, Ettore; Altucci, Lucia; et al.
<x xml:space="preserve">Abstract</x> The front cover picture shows the 3D homology model of the second catalytic subunit CDII of HDAC6 in complex with a selective tert‐butylcarbamate‐containing inhibitor as predicted by docking calculations. The protein is represented as yellow ribbons while the ligand as green sticks. When tested against a wide panel of different cancer cell lines (four of them are represented as "planets" in the front cover picture), this compound and its structural congeners showed low or single‐digit micromolar antiproliferative effect. Remarkably, against neuroblastoma cell lines, these HDAC inhibitors (HDACis) exerted growth inhibition at nanomolar level, suggesting an additional role for HDAC6 inhibition in neurologic diseases. For more details, see the Full Paper by Lucia Altucci, Donatella Del Bufalo, Antonello Mai, Sandro Cosconati et al. on p. 800 ff.<boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>